(3GdefjI hGdCed aj TQM cJGH Gdedd hGdfMds - (3CMeO Hf jMji Hf GdeQJVj GdRjOj,J (B840 (3g` s
(3ChdgG (B:s
(3Gddge Ef CLd GdKfGA jbUQ Yf hUa LdGdc , hGYXe GdNVhY jbd Yf ELdGdc , hChaQ GdTcQ dGjai HYTjQ eYTGQ EMSGfc s
(3BNQgG (B:s
(3abO UGQ GdKhGHGf eJMHWjf hEf JaGVdGhgPG hGVM ceG JQi hHJeGe gPg GdLedI Je cJGH hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3fSNI CNQis
(3cJHJ GdYfGhjf HGdMeQI s
(3GdfSNI ebGHdI Ydi fSNI UMjMI ebGHdI Ydi fSNI GdeUfa s
(3HBNQgG bQGAI MOjKI s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdESdGejs